PERAN MENDONGENG DALAM PEMBENTUKAN POLA BERFIKIR KRITIS ANAK USIA 5-6 TAHUN DI TK AL IHSAN JERU TUREN - Norma Ita Sholichah; Siti Nur Khasanah (LP3M Universitas Al-Qolam Malang, 2026)
Early childhood is known as the golden age, a crucial period in child development characterized by rapid brain cell growth and cognitive abilities. The purpose of this study is to determine the role of storytelling in the formation of critical thinking patterns in children aged 5-6 years at Al Ihsan Kindergarten and to determine indicators of critical thinking patterns that can be observed in children after participating in storytelling activities. While the research method used is a qualitative descriptive research method. The results of the study indicate that storytelling can stimulate imagination, curiosity, and children's ability to ask questions, conclude, and provide opinions on the story told. Some indicators of critical thinking that emerged include the ability to ask questions, answer analytical questions, and express opinions based on the storyline. Thus, storytelling has proven effective as a strategy to stimulate the development of critical thinking in early childhood.